Pengaruh Iklan dan Endorser terhadap Brand Awareness serta Dampaknya pada Keputusan Pembelian - Setiawan, Budi; Rabuani, Celia Celesta (RISET: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2019)
The aim of this research is to analyze the influence of brand and endorser to brand awareness and its impact to purchase decision. The authors try to fulfill the research gap that exist, i.e. combining the brand and endorser in order to predict the brand awareness, that in our best knowledge still has less attention from researchers. Research samples a number of 100 respondents, were selected through non-random sampling technique, i.e. purposive sampling. Survey method was selected with questionnaire as a tool to gain primary data. Based on the path analysis results that has ben conduct, it’s revealed two sub-structure path equation Y = 0,585X1 + 0,229X2 and Z = 0,237X1 + 0,108X2 + 0,510Y. Both brand and endorser, it’s significantly proven influencing of the brand awareness. The consumer purchase decision significantly formed by the brand awareness as the antecedent that formed by brand and endorser. This research revealed a gap that need to be revised in the next research. Endorser failed to become antecedent of consumer purchase decision. So it will be need a better measurement, to make sure that consumer purchase decision were also can be formed by endorser.